Α6β2 subunit containing nicotinic acetylcholine receptors exert opposing actions on rapid dopamine signaling in the nucleus accumbens of rats with high-versus low-response to novelty. (November 2017) - Siciliano, Cody A.; McIntosh, J. Michael; Jones, Sara R.; Ferris, Mark J.
Abstract: Determining neurobiological factors that contribute to individual variance in drug addiction vulnerability allows for identification of at-risk populations, use of preventative measures and personalized medicine in the treatment of substance use disorders. Rodents that exhibit high locomotor activity when exploring an inescapable novel environment (high-responder; HR) are more susceptible to the reinforcing effects of many abused compounds, including nicotine, as compared to animals that exhibit low locomotor activity (low-responder; LR). Given that nicotinic acetylcholine receptor (nAChR) modulation of reward-related dopamine signaling at accumbal dopamine terminals is critical for the acquisition of drug self-administration, we hypothesized that nAChR modulation of dopamine release would be predicted by an animal's novelty response. Using voltammetry in the nucleus accumbens core of rats, we found that nicotine produced opposite effects in HR and LR animals on stimulation frequencies that model phasic dopamine release, whereby release magnitude was either augmented or attenuated, respectively. Further, nicotine suppressed dopamine release elected by stimulation frequencies that model tonic release in LR animals, but had no effect in HR animals. The differential effects of nicotine were likely due to desensitization of nAChRs, since the nAChR antagonists mecamylamine (non-selective, 2 μM), dihydro-beta-erythroidine (β2-selective, 500 nM), and α-conotoxin MII [H9A; L15A] (α6-selective, 100 nM) produced effects similar to nicotine. Moreover, dihydro-beta-erythroidine failed to show differential effects in HR and LR rats when applied after α-conotoxin MII [H9A; L15A], suggesting a critical role of α6β2 compared non α6-containing nAChRs in the differential effects observed in these phenotypes. These results delineate a potential mechanism for individual variability in behavioral sensitivity to nicotine. Highlights: Nicotine augments phasic dopamine signaling in animals with high response to novelty. Nicotine attenuates phasic and tonic dopamine signaling in animals with low response to novelty. Nicotine attenuates locomotor activity to a greater extend in animals with low response to novelty. Differential nicotine actions are likely due to desensitization of α6β2-containing nicotinic receptors.